PENYUSUNAN FEATURE MODEL DENGAN PENDEKATAN FODA. STUDI KASUS APLIKASI ELEARNING UNIVERSITAS MERCUBUANA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
One of the roles in information and communication technology to improve the quality of learning and teachingin educational organizations is to conduct a web-based learning facility that e-learning. In general, there are two types of software that is generic and bespoke (customized), in this study we found that the university mercubuana customized using generic applications. Featured model is a way to define the functionality of the application based on the features required by user features, the features of these features can be grouped based on necessity (mandatory) and supplementary (optional). Preparation of requirements-based features proposed in this study is intended as the reference management application requirements e-learning mapped clearly and well. So it can be helpful to the development of future applications.